2016
DOI: 10.1016/j.plantsci.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

CIPK23 is involved in iron acquisition of Arabidopsis by affecting ferric chelate reductase activity

Abstract: Iron deficiency is one of the major limiting factors affecting quality and production of crops in calcareous soils. Numerous signaling molecules and transcription factors have been demonstrated to play a regulatory role in adaptation of plants to iron deficiency. However, the mechanisms underlying the iron deficiency-induced physiological processes remain to be fully dissected. Here, we demonstrated that the protein kinase CIPK23 was involved in iron acquisition. Lesion of CIPK23 rendered Arabidopsis mutants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 72 publications
1
51
0
Order By: Relevance
“…This protein forms a calcium‐sensing complex with CBL1 or CBL9 (CALCINEURIN B‐LIKE PROTEIN), which is involved in iron, nitrate and potassium transport and sensing (Léran et al . ; Manik et al ; Tian et al ). Its role in regulating nitrate transport and signalling by the NITRATE TRANSPORTER 1.1 (NRT1.1) transceptor (duel nutrient transport/signalling function) and the crucial role this plays in the regulation of ABA levels in seeds is well characterized (reviewed in Finch‐Savage and Footitt ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein forms a calcium‐sensing complex with CBL1 or CBL9 (CALCINEURIN B‐LIKE PROTEIN), which is involved in iron, nitrate and potassium transport and sensing (Léran et al . ; Manik et al ; Tian et al ). Its role in regulating nitrate transport and signalling by the NITRATE TRANSPORTER 1.1 (NRT1.1) transceptor (duel nutrient transport/signalling function) and the crucial role this plays in the regulation of ABA levels in seeds is well characterized (reviewed in Finch‐Savage and Footitt ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, Col‐0 and cipk23 lose light but not nitrate sensitivity during induction of secondary dormancy suggesting that loss of nitrate sensitivity is related to NRT1.1 protein levels and the action of factors such as DOG1 that regulate deep dormancy (reviewed in Finch‐Savage and Footitt ). CIPK23‐CBL complexes also have other functions, for example, as nutrient sensors to monitor mineral homeostasis in general (Tian et al ). Further work is therefore needed to fully understand the role of CIPK23 in dormancy regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to AKT1/AtKC1 (Arabidopsis K + Channel 1) and HAK5 potassium uptake systems a single nitrate ‘transceptor’ CHL1 (NRT1.1; Nitrate transporter 1.1; NPF6.3) mediates both high‐affinity and low‐affinity nitrate uptake depending on its phosphorylation status at threonine residue 101 mediated by CIPK23 (Liu & Tsay, ; Léran et al ., ). In addition, it was recently shown that CIPK23 activates iron transport in Arabidopsis roots but inhibits AMT1;2 (ammonium transporter 1;2) mediated NH 4 + uptake in Arabidopsis roots to avoid toxic accumulation of cytoplasmic ammonium (Tian et al ., ; Straub et al ., ) (Fig. ).…”
Section: The Ca2+ Decoding Toolkit In Plantsmentioning
confidence: 99%
“…Tansley review New Phytologist activates iron transport in Arabidopsis roots but inhibits AMT1;2 (ammonium transporter 1;2) mediated NH 4 + uptake in Arabidopsis roots to avoid toxic accumulation of cytoplasmic ammonium (Tian et al, 2016;Straub et al, 2017) (Fig. 1).…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, CIPK23 regulates the acquisition of other nutrients. The NH 4 + transporters AMT1;1 and AMT1;2 are inactivated by CIPK23‐mediated phosphorylation at high NH 4 + concentrations, avoiding toxic NH 4 + accumulation (Straub et al ), and the CBL1/CBL9‐CIPK23 complexes are also involved in Fe acquisition by affecting ferric chelate reductase activity (Tian et al ). In conclusion, CIPK23 emerges as an interesting hub for general plant nutrition.…”
Section: Signaling Of K+ and No3− Po43− And So42− Deficienciesmentioning
confidence: 99%